Digital learning media-practices in integrated-science and social-studies under the independent curriculum in elementary schools - Adi, Fadhil Purnama; Marmoah, Sri; Atmojo, Idam Ragil Widianto; Matsuri, Matsuri; Ardiansyah, Roy; Saputri, Dwi Yuniasih; Rosyid, Haniifah Alyaa Azmiira (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
This study aims to describe the use of digital learning media in the IPAS subject (a combination of science and social studies) within the implementation of the independent curriculum in elementary schools. This research employs a descriptive qualitative design. The findings show that the use of digital learning media has been implemented effectively, meeting various educational media criteria. The selection of digital learning media follows the ACTION model (Access, Cost, Technology, Interactivity, Organisation, Novelty), although certain aspects like access and technology remain suboptimal. This study is expected to contribute to the development of more effective learning theories for digital media and to enrich knowledge about digital learning media appropriate for early childhood development. This study contributes to digital learning media analysis in elementary education by examining the use of digital media in the IPAS subject within the Independent Curriculum framework using the ACTION model. The findings highlight both effective implementation and persistent challenges in access and technology, offering practical guidance for selecting age-appropriate digital learning media in elementary schools.